The identity and separateness of lexical meaning: case study of the English word tail - Tur, Vitali V. (Journal of the Belarusian State University. Philology, 2020)
A semantic corpus-based study of the English word tail is carried out providing insight into the reasons of vagueness of word meaning boundaries. Based on the data revealing the most frequent words used with the word tail, it is concluded that word senses may be entrenched on different levels of their schematization. The article demonstrates that senses can be linked by relations of inclusion – certain units of meaning can function as separate word senses and at the same time be variants of a single, more general meaning. The regularities of the schematization of the word tail are exposed according to which, as far as category features get generalized, so does the relevance of non-category features increase: location (hindmost position), spatial (extension in space), perceptual (form), partial (part of the whole) features. A choice of the features predetermines general directions of the word meaning schematization. It is argued that word sense boundaries are flexible resulting in the relative nature of the notions of polysemy and monosemy, which appear to be the functions of meaning schematization.